A Study of Dust Accumulating Process on Solar Photovoltaic Modules with Different Surface Temperatures. (August 2015) - Jiang, Yu; Lu, Lin
Abstract: This paper experimentally investigated the dust particle deposition onto solar photovoltaic (PV) modules to examine the effect of temperature gradient (thermophoresis) on dust accumulation process under different operating temperatures. The measured deposition densities of dust particles were found to range from 0.50 mg/m 2 to 0.84 mg/m 2 under the experimental conditions. The PV module with higher surface temperature has a lower density due to the effect of thermophoresis force arising from the temperature gradient between its surface and the surrounding air. Moreover, the energy output ratios were found to increase from 0.947 to 0.971 with the increase of temperature gradient, showing the same effect of thermophoresis force as particle deposition density. In addition, the most obvious temperature gradient for the thermophoresis force was found to be lower than 40 o C. This work will help the engineers to understand the reduced impact of high surface temperature of solar cells on dust particle deposition process.